2018
DOI: 10.1371/journal.pone.0202735
|View full text |Cite
|
Sign up to set email alerts
|

Towards improved health service quality in Tanzania: An approach to increase efficiency and effectiveness of routine supportive supervision

Abstract: Effective supportive supervision of healthcare services is crucial for improving and maintaining quality of care. However, this process can be challenging in an environment with chronic shortage of qualified human resources, overburdened healthcare providers, multiple roles of district managers, weak supply chains, high donor fragmentation and inefficient allocation of limited financial resources. Operating in this environment, we systematically evaluated an approach developed in Tanzania to strengthen the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…These two points will however be investigated in a subsequent paper [35]. The study did additionally not demonstrate how the approach was able to increase more generally the feasibility of routine supportive supervision, but this was shown elsewhere [36]. Finally, none of the studies examined the effects of the e-TIQH assessment tool or improvements in quality of care on changes in health outcomes.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…These two points will however be investigated in a subsequent paper [35]. The study did additionally not demonstrate how the approach was able to increase more generally the feasibility of routine supportive supervision, but this was shown elsewhere [36]. Finally, none of the studies examined the effects of the e-TIQH assessment tool or improvements in quality of care on changes in health outcomes.…”
Section: Discussionmentioning
confidence: 96%
“…Overall, the results presented here together with previously reported findings [34] strongly suggested that the e-TIQH assessment tool, which focused on processes and structural adequacy of healthcare, is accurate enough to assess and monitor quality of primary healthcare for the purpose of routinely steering improvement measures. In practice, its ability to measure quality of care over time reflected a feasible approach to be used during supportive supervision and received great support from the CHMTs and health facilities staff [36]. However, the value of the e-TIQH assessment tool would need to be carefully reassessed if it were to be used outside its intended purpose.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations